Neutralizing Mutations Significantly Inhibit Amyloid Formation by Human Prion Protein and Decrease Its Cytotoxicity. Issue 4 (14th February 2020) - Huang, Jun-Jie; Li, Xiang-Ning; Liu, Wan-Li; Yuan, Han-Ye; Gao, Yuan; Wang, Kan; Tang, Bo; Pang, Dai-Wen; Chen, Jie; Liang, Yi
Abstract: Prion diseases, such as Creutzfeldt–Jakob disease and bovine spongiform encephalopathy, are fatal neurodegenerative diseases that affect many mammals including humans and are caused by the misfolding of prion protein (PrP). A naturally occurring protective polymorphism G127V in human PrP has recently been found to significantly attenuate prion diseases, but the mechanism has remained elusive. We herein report that the hydrophobic chain introduced in G127V significantly inhibits amyloid fibril formation by human PrP, highlighting the protective effect of the G127V polymorphism. We further introduce an amino acid with a different hydrophobic chain (Ile) at the same position and find that G127I has similar protective effects as G127V. Moreover, we show that these two neutralizing mutations, G127V and G127I, significantly decrease the human PrP cytotoxicity resulting from PrP fibril formation, mitochondrial damage, and elevated reactive oxygen species production enhanced by a strong prion-prone peptide PrP 106-126. These findings elucidate the molecular basis for a natural protective polymorphism in PrP and will enable the development of novel therapeutic strategies against prion diseases. Graphical abstract: Image 1 Highlights: Neutralizing mutations modulate the liquid-liquid phase separation of the normal cellular prion proteinPrP. Neutralizing mutations significantly inhibit the fibrillization of prion protein (PrP). Neutralizing mutations protect against mitochondrial damage in cells. Neutralizing mutations decrease reactive oxygen species production and cytotoxicity of PrP.